2019
DOI: 10.1186/s12711-019-0476-4
|View full text |Cite
|
Sign up to set email alerts
|

Using imputed whole-genome sequence data to improve the accuracy of genomic prediction for parasite resistance in Australian sheep

Abstract: Background This study aimed at (1) comparing the accuracies of genomic prediction for parasite resistance in sheep based on whole-genome sequence (WGS) data to those based on 50k and high-density (HD) single nucleotide polymorphism (SNP) panels; (2) investigating whether the use of variants within quantitative trait loci (QTL) regions that were selected from regional heritability mapping (RHM) in an independent dataset improved the accuracy more than variants selected from genome-wide association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 33 publications
8
51
0
2
Order By: Relevance
“…They were then imputed to the sequence level one chromosome at a time, using whole genome sequence data of a reference population of 311 progeny tested Hanwoo bulls [1], resulting in a total of 27,980,473 SNPs; the imputation pipeline followed for imputing from 770K to the sequence level was the same as the one used for 50K to HD imputation. Following a previous study [32], only SNPs with Minimac3 imputation quality statistic (R 2 ) higher than 0.4 were retained for further analysis, resulting in a total of 12,980,473 SNPs. The overall average imputation accuracy, post quality control (R 2 ) was 0.76, which was similar to a previously reported study [33].…”
Section: Snp Genotyping Imputation and Filtering For Regulatory Snpsmentioning
confidence: 99%
“…They were then imputed to the sequence level one chromosome at a time, using whole genome sequence data of a reference population of 311 progeny tested Hanwoo bulls [1], resulting in a total of 27,980,473 SNPs; the imputation pipeline followed for imputing from 770K to the sequence level was the same as the one used for 50K to HD imputation. Following a previous study [32], only SNPs with Minimac3 imputation quality statistic (R 2 ) higher than 0.4 were retained for further analysis, resulting in a total of 12,980,473 SNPs. The overall average imputation accuracy, post quality control (R 2 ) was 0.76, which was similar to a previously reported study [33].…”
Section: Snp Genotyping Imputation and Filtering For Regulatory Snpsmentioning
confidence: 99%
“…This is also in line with results of GP in this thesis using the variants pre-selected based on a WGS-based GWAS , and other results in literature e.g. Ober et al 2015;Van Den Berg et al 2016;Al Kalaldeh et al 2019). For example, Al Kalaldeh et al (2019) showed an improvement of between 5% to 9% in the accuracy of multi-breed GP of parasite resistance in Australian sheep, when variants were carefully pre-selected based on their -log10(p) value from a WGS-based GWAS, as compared to scenarios with no variants pre-selection.…”
Section: Using Qtl From a Snp-chip Based Gwassupporting
confidence: 91%
“…Ober et al 2015;Van Den Berg et al 2016;Al Kalaldeh et al 2019). For example, Al Kalaldeh et al (2019) showed an improvement of between 5% to 9% in the accuracy of multi-breed GP of parasite resistance in Australian sheep, when variants were carefully pre-selected based on their -log10(p) value from a WGS-based GWAS, as compared to scenarios with no variants pre-selection. Furthermore, they showed that the improvement in accuracy was more pronounced when variants were pre-selected from WGS-based GWAS as compared to when variants were pre-selected from a GWAS based on a high density (HD) SNP panel.…”
Section: Using Qtl From a Snp-chip Based Gwasmentioning
confidence: 99%
“…Contrary to those ndings, our study showed no signi cant increase in prediction accuracy when using WGS variants as opposed to SNP from the HD. Other authors have also observed lower or no signi cant bene ts in predictive ability gain using sequence data comparing with SNP arrays [6,9,10,12,45,49,50].…”
Section: Predictive Abilitymentioning
confidence: 98%